Marketing Strategies in Increasing Sales of Tomoro Coffeshop at Tanjung Duren - Maharani, Sari; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research aims to see how to increase Tomoro Tanjung Duren coffee shop sales. If previously it was only a shop that offered coffee drinks, it now has a wider function. We can see this from the current cafe building designs; apart from being made as comfortable as possible, they are also made as attractive as possible to attract young people. Hanging out in cafes has now become something often found in big cities and is closely related to various groups, both upper and middle class, with ages ranging from teenagers to adults. This can be seen from the recent increase in cafes or coffee shops. With the current number of outlets, the total profit of coffee shops in Indonesia has reached IDR 4.8 trillion. Lifestyle changes, which are increasingly sophisticated and fast-paced, are seen as an opportunity for business people and cafe industry players to take advantage of this moment.